Analysis of Carpet Orders to Suppliers at PT Distributor Karpet Bandung (dkb) Using Probabilistic Economic Order Quantity - Waskito, Saptono Kusdanu; Rahayu, Muji (Dinasti Publisher, 2023)
PT Distributor Karpet Bandung (DKB) is a distribution services company that sells Eva Carpets in the city of Bandung. DKB purchased Eva Carpets from Suppliers in Jakarta. The number of Eva Carpet purchases in 2023 will be as much as Eva Carpet sales in 2023 will be 106,614 units, 107,000 units. The initial inventory in 2023 will be 500 units. There is excess inventory of 886 units. The author conducted research with the title